Applying no-depletion equilibrium sampling and full-depletion bioaccessibility extraction to 35 historically polycyclic aromatic hydrocarbon contaminated soils. (May 2018) - Bartolomé, Nora; Hilber, Isabel; Sosa, Dayana; Schulin, Rainer; Mayer, Philipp; Bucheli, Thomas D.
Abstract: Assessing the bioaccessibility of organic pollutants in contaminated soils is considered a complement to measurements of total concentrations in risk assessment and legislation. Consequently, methods for its quantification require validation with historically contaminated soils. In this study, 35 such soils were obtained from various locations in Switzerland and Cuba. They were exposed to different pollution sources (e.g., pyrogenic and petrogenic) at various distance (i.e., urban to rural) and were subject to different land use (e.g., urban gardening and forest). Passive equilibrium sampling with polyoxymethylene was used to determine freely dissolved concentrations (Cfree ) of polycyclic aromatic hydrocarbons (PAHs), while sorptive bioaccessibility extraction (SBE) with silicone rods was used to determine the bioaccessible PAH concentrations (Cbioacc ) of these soils. The organic carbon partition coefficients of the soils were highest for skeet soils, followed by traffic, urban garden and rural soils. Lowest values were obtained from soil exposed to petrogenic sources. Applicability of SBE to quantify Cbioacc was restricted by silicone rod sorption capacity, as expressed quantitatively by the Sorption Capacity Ratio (SCR); particularly for soils with very high KD . The source of contamination determined bioaccessible fractions (fbioacc ). The smallest fbioacc were obtained with skeet soils (15%), followed by the pyrogenically influenced soils, rural soils, and finally, the petrogenically contaminated soil (71%). In conclusion, we present the potential and limitations of the SBE method to quantify bioaccessibility in real soils. These results can be used for additional development of this and similar bioaccessibility methods to guarantee sufficient sorption capacity to obtain reliable results. Graphical abstract: Image 1 Highlights: Sufficient passive sampling sorption capacity is crucial for quality assurance. Pollutant source type dominated KD and bioaccessible concentrations. Lowest bioaccessible fractions (15% on average) were found in skeet contaminated soils. Petrogenic polluted soil had the highest bioaccessible fractions (71% on average). Abstract : Freely dissolved concentrations and bioaccessible fractions of PAHs in soils depended on pollutant source and site characteristics, while the sink capacity was limiting during bioaccessibility extractions of soils with low PAH content and high KD values.